Involvement of Technical Reasoning More Than Functional Knowledge in Development of Tool Use in Childhood - Remigereau, Chrystelle; Roy, Arnaud; Costini, Orianne; Osiurak, François; Jarry, Christophe; Le Gall, Didier (Frontiers in Psychology, 2016)
It is well-known that even toddlers are able to manipulate tools in an appropriate manner according to their physical properties. The ability of children to make novel tools in order to solve problems is, however, surprisingly limited. In adults, mechanical problem solving has been proposed to be supported by “technical reasoning skills,” which are thought to be involved in every situation requiring the use of a tool (whether conventional or unusual). The aim of this study was to investigate the typical development of real tool use skills and its link with technical reasoning abilities in healthy children. Three experimental tasks were adapted from those used with adults: mechanical problem solving (three different apparatus), real tool use (10 familiar tool-object pairs), and functional knowledge (10 functional picture matching with familiar tools previously used). The tasks were administered to 85 healthy children divided into six age groups (from 6 to 14 years of age). The results revealed that real tool use (p = .01) and mechanical problem solving skills improve with age, even if this improvement differs according to the apparatus for the latter (p < .01 for the Hook task and p < .05 for the Sloping task). Results also showed that mechanical problem solving is a better predictor of real tool use than functional knowledge, with a significant and greater weight (importance weight: 0.65; Estimate±Standard Error: 0.27±0.08). Ours findings suggest that real tool use and technical reasoning develop jointly in children, independently from development of functional knowledge. In addition, technical reasoning appears partially operative from the age of 6 onwards, even though the outcome of these skills depends of the context in which they are applied (i.e., the type of apparatus).